The ethnopolitcs of Moro self-determinaton in the Philippines: So litle, too late? - Buendia, Rizal G. (Animo Repository, 2012)
The paper re-examines the Moro secessionist movement in the Philippines from the perspective of ethno-politics. Using a hybrid framework, which combines Paul Brass' and Abner Cohen's instrumentalist approach to ethnicity on the one hand and Michael Hechter's and Michael Banton's rational choice theory on the other hand, the paper argues that the complexity of the current separatist war is not simply due to the weakness of the state but also due to the weakness of the Bangsamoro identity and notion of nationhood. This frailty allows the state to co-opt leaders of the movement and sabotage their legitimate quest to self-governance and political autonomy. The reinvention of the Moro struggle towards self-determination reflects another attempt to sustain the relevance of the Muslims' effort to create its own nation-state. However, the prospect of which is not promising. Addressing the conflict in Mindanao requires not only the strengthening of the state but also the strengthening of the Moro national identity. Mutually re-enforcing these strengths can accelerate the process of Philippine nation-state building and establish co-governance mechanisms that would guarantee the unification of the country in spite of its diversity. © 2012 De La Salle University, Philippines.